Theory-Based Roadmap for Assessing Sustainability in the Collaborative Economy - Sun, Shouheng; Ertz, Myriam (Frontiers in Psychology, 2021)
This study aims to investigate the current state of sustainability for the collaborative economy (CE). By utilizing the triple bottom line as a founding conceptual framework, the study summarizes and discusses the sustainability of the CE from three dimensions: environment, economy, and society. The study further proposes some targeted measures and suggestions to measure the level of sustainability of the CE and CE platforms. The result shows that the CE has partially fulfilled some of its initial promises pertaining to sustainability, such as creating new job opportunities, economic growth, the efficient use of space and physical resources, as well as social mixing. However, the current sustainability benefits remain much smaller than some claim and hope for. Therefore, governments, platforms, and the public should work together to solve current challenges pertaining to the CE to tap its sustainability potential.